Recent Trends in Inflation in India - Jerry Alwin (RESEARCH ESSENCE, 2013)
The Paper presents the conceptual and theoretical issues of inflation, recent trends, causes and consequences of Inflation in India and measures to control inflation for the period 2006-07 to 2011-12. The available evidence suggests that major contributing factors of inflation are rise in crude oil prices, depreciation of the rupee, reduction in food grain production and diversion of agricultural land for commercial crops and high price of manufactured products. In spite of the various measures taken by the government the rate of inflation is not fully under control.